ENERGI LAPLACIAN SKEW PADA DIGRAF - Fitria Dewi Puspitasari; Bayu Surarso (MATEMATIKA FSM, UNDIP, 2012)
Digraph G is a pairs of set (V,Γ) , with V(G) is set of vertices G , and Γ(G) is set of arc G . Graph G can be representated in to matrix adjacencyS(G) , from matrix S(G) be obtained eigenvalues of graph G . The sum of the absolute values of its eigenvalues is energy skew of digraph G . From digraph G be obtained DG=diag(d1,d2,d3,…,dn) the diagonal matrix with the vertex degrees d1,d2,d3,…,dn of v1,v2,v3,…,vn . Then LG=DG-S(G) is called the laplacian matrix of digraph G . The sum of the quadrate values of each eigenvalues is energy laplacian skew. In this final project will explain about the concept of the skew laplacian energy of a simple, conected digraph G . Also find the minimal value of this energy in the class of all connnected digraphs on n≥2 vertices.